МEDIA, MIGRATION AND TERRORISM - SOME CORRELATIONS - Subotic, Milovan (Serbian political thought, 2025)
How do contemporary media approach the phenomena of migration and terrorism and their correlation? What factors contribute to the increased media attention given to news related to terrorism and migration? What are the experiences of the academic community studying these phenomena in the United States, Europe, and more specifically, in the Mediterranean gateway countries of Europe – Italy, Spain, and Greece? How does the rise in irregular entries into Europe truly impact the number of terrorist attacks affecting European countries, as well as their intensity and the number of casualties resulting from such incidents? These are some of the research questions this paper seeks to address. Drawing on available literature concerning media and academic treatments of terrorism and migration, as well as insights into their similarities and differences, contradictions and paradoxes, this study concludes that, despite media portrayals often marked by sensationalism and spectacle, academic analyses of these phenomena and their correlation do not provide unambiguous confirmation that a greater influx of irregular migration into Europe directly leads to a higher number of terrorist attacks and/or an increased number of casualties on European soil.
Keywords: terrorism; migrations; media; reporting; radicalization; correlation